Tetraphenylethylene substituted thienothiophene and dithienothiophene derivatives: synthesis, optical properties and OLED applications. Issue 23 (18th May 2020) - Isci, Recep; Tekin, Emine; Kaya, Kerem; Piravadili Mucur, Selin; Gorkem, Sultan Funda; Ozturk, Turan
Abstract : TPE units at the periphery of two TTs and a DTT affect the structures, properties and OLED characteristics of these three synthetically easily accessible novel conjugated compounds for materials chemistry. Abstract : Thieno[3, 2- b ]thiophene (TT) and dithieno[3, 2- b ;3, 2- d ]thiophene (DTT) have drawn immense attention in the field of electronics and optoelectronics. In this work, the first examples of TTs (TPE2-TT and TPE3-TT ) and a DTT (TPE2-DTT ), having tetraphenylethylene (TPE) at the periphery exhibiting aggregation induced emission (AIE) in OLEDs, were designed and synthesized by the Suzuki coupling reaction. Their properties were investigated through experimental and computational studies, as well as X-ray diffraction and DFT optimization. TPE2-TT showed excellent device performance with a maximum luminance of 11 620 cd m −2, a maximum current efficiency of 6.17 cd A −1 and a maximum external quantum efficiency of 2.43%. Moreover, these synthetically easily accessible molecules have high thermal stability, which makes them perfectly suitable for optical applications.